Tobacco Price Elasticity and Tax Progressivity in Moldova - Fuchs, Alan; Meneses, Francisco (World Bank, Washington, DC, 2018)
Tobacco-use–related diseases are the main cause of mortality in Moldova, where tobacco consumption is widely spread, especially among men. In addition to health concerns, tobacco consumption has economic consequences, as households spend substantial resources on tobacco and related out-of-pocket medical costs. Tobacco tax increases are one of the most effective measures to reduce tobacco consumption, but are usually believed to be regressive, taxing the poor proportionally more than the rich. This paper estimates the tobacco price elasticity of demand for Moldova by income decile and undertakes an extended cost-benefit analysis to estimate the distributional effect of a rise in tobacco taxes on income distribution. The paper's main findings are that a tobacco price increase would generate a rise in expenditure deriving from direct tobacco price increases, but would reduce the costs of out-of-pocket medical expenses. Based on these two factors, the net effect of a tobacco tax increase would be progressive in the analyzed cases, ultimately benefitting the incomes of the lower-income groups in the population.